Evolution of Baffin Bay Water Masses and Transports in a Numerical Sensitivity Experiment under Enhanced Greenland Melt. Issue 3 (27th May 2017) - Grivault, Nathan; Hu, Xianmin; Myers, Paul G.
ABSTRACT: We used a numerical model forced with three different scenarios to analyze Baffin Bay circulation sensitivity to runoff around Baffin Bay, especially the Greenland runoff, for the past (1970–2010) and future (2010–2099). We observed an overall decrease in transport from the Arctic to the North Atlantic for the volume, heat, and freshwater over the time period as well as an augmentation of the freshwater and heat in Baffin Bay. In the early 1990s, the increase in heat in Baffin Bay was consistent with an increase in the West Greenland Irminger Water (WGIW) inflow at Davis Strait while later West Greenland Shelf Water played an important role in the heat import, sustaining the idea that the West Greenland Current might have an impact on the melt of West Greenland tidewater glaciers. The increase in freshwater and later in heat in Baffin Bay leads to changes in the steric height inside Baffin Bay, which leads to changes in the circulation. After 1978, the WGIW reaches the North Water polynya and recirculates into the Baffin Bay gyre where it accumulates over time. In the future experiment, the dynamic changes in Baffin Bay are mainly related to the accumulation of heat inside the gyre.